The expansion of tree-based boom crops in mainland Southeast Asia: 2001 to 2014. Issue 1 (4th March 2018) - Hurni, Kaspar; Fox, Jefferson
ABSTRACT: Over the past half century, countries of Mainland Southeast Asia (MSEA) – Cambodia, Laos, Myanmar, Thailand, and Vietnam – have witnessed increases in commercialized agriculture with rapid expansions of boom-crop plantations. We used MODIS EVI and SWIR time-series from 2001–2014 to classify tree-cover changes across MSEA and performed a supervised change detection using an upscaling approach by deriving samples from existing Landsat classifications. We used the random forest classifier and distinguished 24 classes (16 representing boom-crops) with an accuracy of 82.2%. Boom-crops occupy about 18% of the landscape (8% of which is rubber). Since 2003 74, 960 km 2 of rubber have been planted; 70% of rubber is planted on former forest land, and 30% on low vegetation area (mainly former croplands). Timing, patterns of change, and deforestation rates, however, differ among the MSEA countries and the high spatial and temporal detail of our classification allowed us to quantify dynamics and discuss political and socio-economic drivers of change.